What is the uptake rate of breast self-examination in Iranian women? Estimation based on systematic review and meta-analysis - Bahman Ahadinezhad; Omid Khosravizadeh; Sima Rafiei; Nastaran Habibi; Zahra Karimkhani; Aisa Maleki (BMC, 2023)
Abstract Background Breast self-examination is a simple, painless, confidential and inexpensive screening method for early diagnosis that does not require specialized tools and equipment. In this study, we have estimated the pooled percentage of breast self-examination (BSE) in Iranian women. Methods All the published literatures between 2012 and 2022 have been reviewed. Searches were performed in PubMed, Web of Science, ProQuest, Science Direct, Google Scholar, Scientific Information and Magiran databases. The effect size was the pooled percentage of breast self-examination (BSE). In order to check the heterogeneity, the estimation of the I2 index and extraction of the Galbraith plot were used, and the drivers of heterogeneity have been identified through meta-regression and estimates were made based on subgroups. All the analysis was done in STATA 15. Results From the initial 294 records, 38 were included in the final analysis in which 9960 women have been studied. The heterogeneity of the studies was high based on the variation in OR (I2 = 98.4%, heterogeneity X2 = 2278.21 (d.f. = 37), p < 0.01). The pooled rate of BSE based on fixed and random methods was obtained as 15.46 (95% CI: 14.83 to 16.09) and 24.74 (95% CI: 19.62 to 29.86) percent, respectively. The highest pooled percentage BSE (39.41%, 95% CI: 30.98 to 47.83) was obtained from studies that investigated the action phase in the Trans theoretical model. The pooled percentage obtained from the studies conducted in the central regions of Iran was higher than other cities (27.47%, 95% CI: 17.38 to 37.55). Conclusion The result from our analysis determined that performing breast self-examination in Iranian women is low. Health policy makers can increase the rate of breast self-examination in Iran by implementing basic educational programs in schools and encouraging and justifying women in social health centers.